Comparison of the promoter sequences of homogentisate geranylgeranyl transferase (HGGT) from high & low vitamin E populations of Tanzanian oil palm (Elaeis guineensis) - Mohd Noor, Muhammad Faris Fazdhli (2013)
Oil palm is widely used in various food applicatons. Palm oil is rich in vitamin E essentialfor human consumption. Variability in the level of vitamin E exists in the oil palm germplasm materials. Tocotrienols and tocophenols are two important forms of vitamin E. In fact, tocotrienols content in Elaeisguineensis are higher compared to tocopherols. Tocotrienol synthesis requires homogenatisegeranylgeranyltransferase (HGGT), which catalyzes the condensation of homogentisate and the unsaturated C20 isopreoidgeranylgeranyldiphosphate (GGDP). Tocopherol differs from tocotrienol because there are three double bonds in the side chain of the tocotrienol. The aim of the study is to detect sequence variation in the form of single nucleotide polymorphism (SNP) by comparing individuals from the Tanzania population that exhibited low and high vitamin E contents. The project involves analyzing the promoter sequence and detecting for variation that falls within important promoter motifs. The genomic structures of the HGGT gene in the germplasm materials were determined. Variation in the gene structure may be exploited for developing PCR-based marker in marker assisted selection to improve vitamin E content of planting materials.